Development of thin film polymer nanocomposite membrane (ZIF-8@PSf/CS) for removal of textile pollutant and evaluating the effect of water samples on human monocytic cell lines (THP-1) using flow cytometer. (1st December 2022) - Gowriboy, N.; Kalaivizhi, R.; Ganesh, M.R.; Aswathy, K.A.
Abstract: The textile industry is responsible for one of the biggest environmental contamination problems in the world because they release unwanted dye effluents. This work proposes the use of polymer materials and nanomaterials in combination to address these difficulties in a variety of ways. In order to create a thin film-based membrane material for the removal of dye pollutants, ZIF-8 nanomaterial has been introduced into poly sulfone (PSf) and Chitosan (CS) blend polymeric material by phase inversion process. The physiochemical characteristics of prepared thin film membrane materials were investigated by using various techniques such as FT-IR, XRD, FE-SEM, AFM, BET, TGA and Mechanical strength analysis. Four common organic dyes Methylene Blue (MB), Rhodamine Blue (Rh. B), Acid Blue (AB) and Congo Red (CR) were used in dye adsorption tests. When the prepared material was tested with a sample of the effluent from the textile industry, the concentrations of all physio-chemical parameters indicated a considerable decrease when comparison to the concentration in the real textile effluent. In addition, the cytotoxicity analysis of the water samples and membrane samples was tested on human monocytic cell lines (THP -1) using flow cytometer. Furthermore, the composition of ZIF-8@PSf/CS membrane material displayed remarkable anti-bacterial characteristics for both gramme positive and gramme negative strains of Staphylococcus aureus and pseudomonas aeruginosa. Graphical abstract: Image 1